O pincel e a pena romântica de François-Auguste Biard - Oliveira, Gustavo Ferreira de (2020)
This research aims to analyze the written and iconographic production by the French artist and traveler François-Auguste Biard, who was in Brazil in 1858-1859. After his return to Europe, he edited and published his travel journal in book format, and also painted some canvases related to the period he was in Brazil. By analyzing the book published by the artist, which narrates his journey through Brazilian territory, we seek to understand how the traveler creates representations about Brazil and its inhabitants, through the socio-cultural context in which the French painter orbited. It was also noted that the canvases produced by Biard dialogue in an expressive way with the figuration that was made of the indigenous people during the 2nd Reign in the search for a national identity. Therefore, this work analyzes and emphasizes the production of the artist in regards to Brazil, seeking to understand the contribution of François-Auguste Biard as a traveler who produced an account about Brazil in the 19th century, as well as a painter who dialogues with the production of a construction of national identity, undertaken by Pedro II